PENINGKATAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN MENGENDALIKAN HAMA TANAMAN MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH DI SMK NEGERI 6 TAKALAR - Nur Aulia Timoasi; Bakhrani Andi Rauf; Muhammad Rais (Jurnal Pendidikan Teknologi Pertanian, 2016)
This research is The act of class research with an approach that oriented to symptoms is natural.This study aims to know the increase in student learning achievements on the subjects of control pests plants subject at students XIagribusiness plantation crops state vocational schools 6 Takalar and thete are 21 students as subject. Problem based learning is one of the method that implement konstruktivistik paradigm in which participants students was introduced to problems in actual so thestudents can draw conclusions from situations that was happening. The results of research, show the finishing of the learning from cycle I of 9,52 % been an increased in results of study in cycle II of 57,15 % so finished in classical be 90,48 % .This shows that the implementation of the problem based learning model (the problem based learning) to increase student learning achievements on the subjects of control pests plants in the class XI agribusiness plantation crops (ATP in state vocational schools 6 Takalar)